Influence of Bionic Waveform Leading Edge Blade on Drag Reduction Characteristics of Mixed Pump - W. Han; J. Zhang; M. Z. Xiao; X. N. Ma; Z. Qu; F. Yin; Q. Sun (Journal of Applied Fluid Mechanics, 2023)
Because the helical axial flow gas-liquid mixing pump has the great advantage of conveying gas-liquid two-phase mixed medium, it has become the main core equipment for deep-sea oil and natural gas exploitation. The gas phase aggregation and bubble movement trajectory in the impeller channel have been widely studied, but the increase of medium flow resistance caused by flow separation has not been deeply discussed. Combined with the Euler multiphase flow model and the SST k-ω turbulence model, the numerical calculation of the helical axial flow gas-liquid mixed pump is carried out. Under design flow conditions Q = 100 m3/h, head H = 30 m, speed n = 4500 r/min, specific speed ns =213.6 r/min, and under different inlet gas content conditions, the influence of the bionic waveform leading edge blade on drag reduction characteristics of the helical axial flow gas-liquid mixed pump was investigated. By designing the blade with a leading-edge structure with different heights and pitches, the separation of the mixed medium and the suction surface is effectively suppressed, and the flow resistance of the medium in the 1/10 area of the inlet end of the blade is reduced. The results show that when the height A is 0.25%L and the pitch λ is 12.5%h, the maximum drag reduction rate in this region is 52.6%, the maximum increase in efficiency of the mixed pump is 2.2%, and the maximum increase in head is 4.8%. This study can provide technical support for flow drag reduction in gas-liquid mixed pump.